Compactly Supra b-k-closed Sets - Ali Hussein, Hanan (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper we advance a modern class of sets called compactly Sb-closed sets and compactly Sb-k-closed sets, and prove that every compactly Sb-k-closed set is compactly Sb-closed set in any supra topological space Z, and the converse is true if Z is supra -space.